Management of Traumatic Perforation of Tympanic Membrane Through Ayurveda (International Journal of Ayurveda and Pharma Research, 2024)
Traumatic tympanic perforations can occur due to various reasons, such as concussion, insertion of objects, temporal bone fractures, barotrauma, etc. Slap injuries are a common cause. Symptoms include sudden conductive deafness, pain and/or blood-stained discharge. Tinnitus and vertigo may complicate the condition. Appropriate and timely management is crucial to reduce the risk of permanent impairment, as studies indicate that spontaneous healing occurs within 1.5 to 3 months. While Ayurvedic texts don’t directly mention traumatic tympanic perforations, they can be categorized as ‘Agantuja Vrana’ (wounds caused by external factors). Ayurvedic treatment includes both local and systemic approaches. In this case study, medicines were used internally for 2 months: Sarivadi Vati, Lakshadi Guggul, Mahayograj Guggul, Gandha Taila capsules and a combination of Vatashamaka Churnas. This combination led to significant improvement; the perforation completely healed in 2 months. Thus, internal use of these drugs helped in the healing of traumatic perforations.